A new approach in PLS/TPS compatibilization using garlic oil: effect on morphological and antioxidant properties - Castro, Maria Cidália Rodrigues (2024)
The packaging industry has made efforts to reduce food waste and improve the resilience of food systems worldwide. Active food packaging, which incorporates active agents, represents a dynamic area where industry and academia have developed new strategies to produce innovative and sustainable packaging solutions that are more compatible with conventional options. Due to health and environmental concerns, industries have sought alternatives to petroleum-based materials and have found biopolymers to be a viable option because of their biodegradable and safe nature. The combination of PLA/TPS has emerged as an effective system for packaging film; however, they are thermodynamically immiscible. This work highlights the development of a starch-based compatibilizer to connect the PLA and TPS phases by functionalizing maize starch with glycidyl methacrylate, glycerol, or garlic oil. Garlic oil was chosen for its plasticizing ability and antioxidant properties. The films produced exhibited excellent compatibility, with enhanced interfacial adhesion between PLA and TPS components. The introduction of compatibilizers also increased the systems’ crystallinity and improved their mechanical properties. The wettability of the films significantly increased with higher garlic oil content, along with enhanced antioxidant properties. These advancements will enable the production of a compatible PLA/TPS system with improved properties for application in the packaging industry.